2021
DOI: 10.1101/2021.11.04.466897
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-wide association analyses of individual differences in quantitatively assessed reading- and language-related skills in up to 34,000 people

Abstract: The use of spoken and written language is a capacity that is unique to humans. Individual differences in reading- and language-related skills are influenced by genetic variation, with twin-based heritability estimates of 30-80%, depending on the trait. The relevant genetic architecture is complex, heterogeneous, and multifactorial, and yet to be investigated with well-powered studies. Here, we present a multicohort genome-wide association study (GWAS) of five traits assessed individually using psychometric mea… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(39 citation statements)
references
References 88 publications
(139 reference statements)
4
32
3
Order By: Relevance
“…This lack of concordance may be partially explained by the fact that the UK Biobank GWASes we used here were run adjusting for head size (Smith et al, 2021), while the ENIGMA meta-analysis did not correct for it (Grasby et al, 2020). Another recent GWAS meta-analysis of reading- and language-related traits (Eising et al, 2021) found a significant genetic correlation between the reading and the CSA of the banks of the superior temporal sulcus (STS), which partially overlaps the lateral STG we report here. They used the same UK Biobank GWAS resouce used in the present study but a different brain parcellation (Smith et al, 2021) to compute the genetic correlations between the reading and language GWAS meta-analysis and 58 structural neuroimaging traits with known links to reading and language.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…This lack of concordance may be partially explained by the fact that the UK Biobank GWASes we used here were run adjusting for head size (Smith et al, 2021), while the ENIGMA meta-analysis did not correct for it (Grasby et al, 2020). Another recent GWAS meta-analysis of reading- and language-related traits (Eising et al, 2021) found a significant genetic correlation between the reading and the CSA of the banks of the superior temporal sulcus (STS), which partially overlaps the lateral STG we report here. They used the same UK Biobank GWAS resouce used in the present study but a different brain parcellation (Smith et al, 2021) to compute the genetic correlations between the reading and language GWAS meta-analysis and 58 structural neuroimaging traits with known links to reading and language.…”
Section: Discussionsupporting
confidence: 58%
“…Genetic variation explains a substantial component of reading abilities, with twin-based heritability (twin-h 2 ) estimates of 0.66 (Andreola et al, 2021) and population-based heritability (SNP-h 2 ) estimates of 0.50 (Verhoef et al, 2020). The largest genome-wide association study (GWAS) of language and reading-related traits to date (N~34,000) has confirmed the robust heritability estimates for these traits, identifying a single genome-wide significant locus for word reading in chromosome 1 (Eising et al, 2021). This study has also highlighted a shared genetic component of reading-related measures with other cognitive components and the cortical surface area (CSA) of the banks of the left superior temporal sulcus (STS; Eising et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The goal of extending these lines of research to other speech, language, and reading traits highlights the need for coordinated efforts toward collecting and meta-analyzing large-scale data in cohorts that have been able to link language-related traits to genotypes. [e.g., GenLang consortium ( genlang.org ): Eising et al, 2021 , BioRXiv , Lancaster et al, in prep. ; International Stuttering Project ( theinternationalstutteringproject.com ): Polikowsky et al, 2021 ; Shaw et al, 2021 ].…”
Section: Introductionmentioning
confidence: 99%